Evaluation of antidiabetic and hepatoprotective activities of ethanolic extract of the fruits of eriobotrya japonica in streptozotocin induced diabetic rats (Funded work) - SABEEHA SHAFI,; NAHIDA TABASSUM, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the present study was to observe the antidiabetic and hepatoprotective activities of ethanolic extract of Eriobotrya japonica fruits in streptozotocin induced diabetic rats. The phytochemical screening of the plant was also done. The animals were divided into five groups. Normal Control group received only the vehicle. Toxic group included those animals in which diabetes was induced by streptozotocin. The 3rd group of animals received streptozotocin and standard antidiabetic drug-glibenclamide. The 4th group included those diabetic animals which received 50 mg/kg b.w dose of fruits of Eriobotrya japonica extract. The 5th group of animals included those diabetic animals which received 100 mg/kg b.w of the plant extract. The biochemical parameters that were evaluated includes blood glucose levels and liver function tests. At the end, the animals were sacrificed and histopathology of pancreas and liver was also done. The results showed significant decrease in blood glucose levels, when treated with two different doses of the plant extract. There was reduction in liver function tests also in animals .The extract of Eriobotrya japonica fruits have shown significant antidiabetic and hepatoprotective activities attributed to its antidiabetic and hepatoprotective potential.